Mini-Review: SARS-CoV-2 and COVID-19 - Dhurgham A .H. Alhasan,; Husein A. Husein Al-Saidy, (University of Thi-Qar Journal of Science, 2021)
On 31 December 2019, the cases of pneumonia caused by unknown etiology had emerged. These cases were reported in Wuhan city, Hubei Province of China. Chinese authorities identified the causative agent and announced to be a novel coronavirus. The tentative name of disease is COVID-19, abbreviating of coronavirus disease-19. The incubation period of the disease ranges from 2 to 14 days, however, 80% of the patients have mild or asymptomatic illness while 15 % and 5% of the patients had exhibited sever and critical cases respectively. The etiology of COVID-19 was known as SARS-CoV-2 and belongs to betacoranviruse as reported by the International Committee on Taxonomy of Viruses (ICTV) especially Coronaviridae Study Group (CSG). In addition, this virus is currently believed to be within bat-coronaviruses besides it possesses a close relationship with SARS-CoV more than MERS-CoV. Although, the majority of the diagnosed patients had symptoms, there were asymptomatic persons who can spread the SARS-CoV-2. Upon the emergence of worldwide distribution of this virus, the WHO had declared it as a global outbreak and pandemic. Unfortunately, at present time, there are neither vaccine and nor an approved COVID-19 specific drug against SARS-CoV-2. One of the remarkable pathogenesis mechanistic step of this virus is taking possession of the affinity to angiotensin-converting enzyme 2 (ACE2). This mini-review summarizes the origin and molecular identification of the virus as well as the host immune responses. SARS-CoV-2 , COVID-19, ACE2, origin